A rare case of congenital methemoglobinemia in pregnancy - Rajmane, Shantanu H.; Anand, Mamta Neelesh; Senapati, J. B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
When iron in haemoglobin is replaced from Fe+2 (ferrous) to Fe+3 (ferric), it leads to formation of methemoglobin. Normal levels of methemoglobin are <1%. This is maintained by redox balance between activity of NADH methemoglobin reductase enzyme and amount of oxidised hemoglobin. When levels of methemoglobin are increased, it leads to methemoglobinemia. Methemoglobin has less affinity to bind to oxygen & results in left shift of oxygen–hemoglobin dissociation curve. As most of the cases of congenital methemoglobinemia are asymptomatic, it is often diagnosed first time during pregnancy. Here we report a case, Primigravida with 38 weeks of gestation posted for emergency LSCS i/v/o meconium-stained liquor, who had SPO2 of 84%, was clinically asymptomatic, vitally stable and with ABG, CXR, ECG and 2DECHO normal. Efforts to find out the cause of reduced oxygen saturation led to diagnosis of rare hemoglobinopathy, methemoglobinemia.